Teachers' Views about the Relevance of Mathematical Learning Prerequisites for Studies in STEM and Beyond (mathematica didactica, 2025)
Mathematics is fundamental to many fields of study, both within and outside STEM. However, many students are not aware of this fact: They often start their studies with wrong or insufficient perceptions about the mathematical requirements for their studies. First-year students' perceptions of the mathematical requirements of different subjects are formed before they start their studies, and teaching and teachers have a significant influence on them. The aim of this article is therefore to examine teachers' perceptions of general and subject-specific mathematical requirements in selected examples of subjects.